Flexural strengthening of reinforced concrete beams using geopolymer-bonded small-diameter CFRP bars. (1st April 2022) - Peng, Kai-Di; Huang, Bo-Tao; Xu, Ling-Yu; Hu, Ruo-Lin; Dai, Jian-Guo
Highlights: A strengthening method using geopolymer-bonded CFRP bars was proposed. Strengthening efficiencies of geopolymer- and epoxy-bonding methods were close. Using short fibers in geopolymer improved the crack resistance of this method. The load capacities of the strengthened members were analytically predicted. A practical application was demonstrated in marine concrete structures. Abstract: In this study, the strengthening system for reinforced concrete (RC) members using geopolymer-bonded small-diameter carbon fiber-reinforced polymer (CFRP) bars was proposed and investigated for the first time. An experimental program was conducted to evaluate the efficiency of the FRP-reinforced geopolymer matrix (FRGM) system for the flexural strengthening of RC beams. A total of 11 RC beams were tested, including ten strengthened beams and one reference beam. The influences of three major factors on the strengthening performance were investigated, including the bonding method (geopolymer vs. epoxy), fiber reinforcement in the matrix (plain geopolymer vs. steel or polyvinyl alcohol fiber-reinforced geopolymer), and the number/diameter of CFRP bars (7Φ3, 2Φ6, and 2Φ10). It was found that the strengthened beams showed significantly higher stiffnesses, yield loads, and ultimate loads than the reference beam and the geopolymer-bonded FRGM layer showed similar strengthening efficiency with the epoxy-bonded FRGM layer. For the FRGM strengthening system, the use of short fibers in the geopolymer matrix further improved the crack control capacity. An analytical investigation was conducted to predict the load capacities of the strengthened beams. Finally, a practical application case was presented to demonstrate the feasibility of this method in strengthening the concrete superstructure at The Port of Zhanjiang (Guangdong, China). The findings lay the groundwork for using this FRGM system to repair reinforced concrete structures.